1995
DOI: 10.1212/wnl.45.6.1161
|View full text |Cite
|
Sign up to set email alerts
|

Incidence and risk factors of vascular dementia and Alzheimer's disease in a defined elderly Japanese population

Abstract: We followed 828 nondemented residents of Hisayama Town, Kyushu, Japan, aged 65 years or older (88.3% of the elderly population) for 7 years starting in 1985 in order to determine the type-specific incidence of dementia and its risk factors in the general Japanese population. Only two subjects were lost to the follow-up, during which period 103 subjects developed dementia. Morphologic examination of the brains of 89 subjects (86.4%) was made by autopsy or CT. We made the initial diagnosis of dementia based on t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

31
483
7
39

Year Published

1997
1997
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 777 publications
(560 citation statements)
references
References 0 publications
31
483
7
39
Order By: Relevance
“…Nevertheless, many other cohorts have reported that physical activities provide protection for future cognitive decline [8,32,[52][53][54][55][56]. In addition, high levels of physical activity were associated with reduced risk of dementia in at least four prospective studies [21,[57][58][59]. Decreased risk for cognitive decline has been reported not only for strenuous [32] but also moderate physical activities [55,57].…”
Section: Physical Activitiesmentioning
confidence: 99%
“…Nevertheless, many other cohorts have reported that physical activities provide protection for future cognitive decline [8,32,[52][53][54][55][56]. In addition, high levels of physical activity were associated with reduced risk of dementia in at least four prospective studies [21,[57][58][59]. Decreased risk for cognitive decline has been reported not only for strenuous [32] but also moderate physical activities [55,57].…”
Section: Physical Activitiesmentioning
confidence: 99%
“…104,[116][117][118] A significant correlation with hypertension exists in all forms of vascular dementia. [118][119][120][121] Other risk factors include increasing age, 122 low education, 123 coronary heart disease, 122,124 atrial fibrillation, 125 diabetes, [126][127][128] transient ischaemic attacks and cerebrovascular accidents, 124 high hematocrit level 120 and smoking. 126 …”
Section: Vascular Dementiamentioning
confidence: 99%
“…94,132,133 In the Hisayama study, hypertension was a risk factor for vascular dementia but not for Alzheimer's disease; the 7-year incidence of vascular dementia decreased in men, along with progress in antihypertensive treatment in Japan, while the prevalence of Alzheimer's disease remained unchanged in men and women suggesting that hypertension does not play a major role in the pathogenesis of Alzheimer's disease in Japanese. 120 In contrast, in Western populations, several studies have suggested that hypertension may play a role in the development of Alzheimer's disease. 118,134 Alzheimer's disease has been reported to be associated with other vascular risk factors 115,135 including coronary heart disease, 136 atrial fibrillation, 125 diabetes mellitus, 127 and white matter lesions.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…Stroke is a leading cause of death 1 and permanent disability in middleaged and elderly people in Japan [2][3][4] as well as in other developed countries. 5 In Japan, the prevalence of obesity has increased rapidly along with the westernization of lifestyle, 6 although it remains considerably lower than that in Western populations.…”
Section: Introductionmentioning
confidence: 99%